Efficacy of a probiotic fermented herb in the prevention and treatment of fish nocardiosis - Li, Weifu; Wu, Yanqi; Su, Qiuxia; Kang, Xu; Li, Yuhao; Ning, Deyu; Xu, Aixuan; You, Xinxin; Huang, Ting; Chen, Jianlin; Lu, Yishan (Frontiers in Veterinary Science, 2026)
Nocardia seriolae poses a severe threat to the sustainable development in the aquaculture of a virous freshwater as well as marine fish species. In the present study, the herb No.100 (it has not been made public due to patent protection) and B. amyloliquefaciens MS-2 with obvious inhibitory effects against N. seriolae strain NS-23 were screened from 190 herbal extracts and 5 probiotic strains for developing probiotic fermented herb (PFH) against nocardiosis in largemouth bass (Micropterus salmoides). An ideal fermentation parameter was established by single-factor optimization as: 4% (w/v) herbal substrate with 4% (v/v) probiotic inoculum at pH 7.5 for 18 h for achieving maximum viable cell count. A 49-day feeding trial with supplements was conducted that the fish with PFH administration were significantly enhanced weight gain rates at 310.51 ± 37.44%, with increasing serum enzyme activities and nitric oxide (NO) levels, up-regulated tissue-specific expression of immune-related genes (TNF-α, IL-8, IL-10, IgM, IFN-γ, IL-1β) as well as mounting up gut microbial diversity (especially Firmicutes and Bacteroidetes species) than that of PBS control, herb or probiotic administration. Furthermore, the challenge study with N. seriolae strain NS-23 was conferred a 77% relative percentage survival (RPS) in the fish with PFH-supplemented diet, and the histopathological analysis confirmed that PFH effectively mitigated multi-organ necrosis and oxidative stress, leading to a complete regression of granulomas in the fish upon artificial challenge. Taken together, this PFH could be served as a safe and effective administrator against fish nocardiosis, offering a sustainable alternative to antibiotics in aquaculture.